Optimisation of the operational parameters during a biological nitrification process using response surface methodology. (24th January 2013) - Darvishi Cheshmeh Soltani, R.; Rezaee, A.; Khataee, A.R.; Godini, H.
Abstract The main aim of this study was to determine the optimal operational parameters for a biological nitrification process. For this reason, a batch mode biological nitrification filled with acclimated sludge was used to remove ammonium from synthetic wastewater. Increasing the initial ammonium concentration from 50 to 300 mg NH4‐N/L within 67 days led to a decrease in the removal efficiency of ammonium from 97.2% to 57.3%, which is equivalent to increasing the specific ammonium oxidation from 1.09 to 3.85 mg NH4‐N/g MLVSS/h. Response surface methodology (RSM) based on central composite design (CCD) was used to evaluate the interactive effects of the three main parameters, including the sodium bicarbonate/ammonium chloride ratio, air flow rate and the reaction time, on the removal of ammonium. For the highest ammonium removal of 98.7%, the optimum sodium bicarbonate/ammonium chloride ratio, air flow rate and reaction time were identified to be 3.48, 3.44 vvm (volume air per volume reactor per minute) and 24.65 h, respectively, based on an initial ammonium concentration of 200 mg NH4‐N/L.